COMPOSITIONAL AND MORPHOLOGICAL EVALUATION OF EDIBLE SALTS: PRELIMINARY RESULTS - Stergiou, C.; Karageorgiou, S.; Theodoridou, S.; Giouri, K.; Papadopoulou, L.; Melfos, V. (Bulletin of the Geological Society of Greece, 2016)
Nutritional habits have as a result the uptake of the elemental content of various foods in the human body. Salt (NaCl) constitutes an integral part of human diet needs. As a consequence, knowledge concerning the composition of edible salt is critical. The aim of the present study is to evaluate the components of 8 edible salt samples that are available in the Greek retail market. Samples were classified according to their color as follows: white (WS1, WS2), black (BS1, BS2), pink (PS1), red (RS1), blue (BLS1) and pale brown (BRS1). The research revealed that all samples mainly consist of Cl and Na. Himalayan Black Salt (BS2) also contains S, whereas the Hawaiian Red Salt (RS1) contains Fe. Additionally, most of the samples contain low levels of Al, Ca, K, Mg, P, S, Si and O as impurities. Concerning the morphological characteristics, salt particles appear irregular, rounded and in two cases as cubic crystals referring to the crystal structure of NaCl. Backscattered images confirm the presence of other mineral phases besides NaCl.